DIFFUSION TENSOR TRACTOGRAPHY IN THE DIAGNOSIS OF CHANGES IN THE CENTRAL DEPARTMENTS OF THE VISUAL ANALYZER IN PRIMARY GLAUCOMA - V. P. Erichev; L. A. Panyushkina; I. A. Novikov; V. S. Reshchikova (Oftalʹmologiâ, 2017)
Purpose. To investigate the potential of diffusion tensor MRT (DT-MRT) in diagnosing the changes of central departments of the visual analyzer in primary open angle glaucoma.Patients and Methods. 16 patients underwent DT-MRT: 12 patients had a prior diagnosis of different stages of glaucoma and 4 acted as controls. Brain examination included both standard (T1, T2, MPR) and special modes (diffusion-weighted imaging with DT tractographic mapping, grey matter morphometry). The main parameter obtained during this exam is fractional anisotropy, which represents brain structures directional organization and integrity. Results. Two main parameters — fractional anisotropy (FA) and fractional anisotropy variability (ΔFA) — were obtained for left and right lateral geniculate body and optic radiation in 3 cross-sections (15–17). We considered FA decrease and ΔFA increase to be the sign of visual pathways integrity loss due to axonal transport defects. Glaucoma patients showed a statistically significant FA decrease in the lower section (FA 14) compared to the control patients (median values 0,74 and 0,77 correspondingly, р<0,01, Mann-Whitney test). FA longitudinal variability of the left hemisphere in the middle section (ΔFA 13) correlated with glaucoma stage as well as retina and optic nerve head morphometric parameters.Conclusion. FA longitudinal variability parameter, obtained with DT-MRT, showed a statistically significant correlation with morphometric and functional of the retina and optic nerve head evaluated with HRT, OCT and SAP perimetry. A high correlation of ΔFA with glaucoma stage indicates the neurodegenerative process spread to the visual centers in the course of disease progression.